Why Study Implicit Religion? An Account of the 27th Denton Conference on Implicit Religion, 7--May 2004 - Parna, Karen (Implicit religion, 2004)
The article reports on a conference on implicit religion held on May 7-9, 2004 at Denton Hall in Yorkshire, England. Implicit religion has been described as the secular quest for meaning in life and is often identified with the pursuit of happiness. Implicit religion and happiness or the personal sense of well-being are indeed closely linked and seem instrumental in the interpretation of each other's modi operandi. From a general, more philosophical point of view scholar Kevin Sharpe discussed the relationship between implicit religion and the pursuit of happiness and called for more research in the area.